Antimetastatic effects of calycosin on osteosarcoma and the underlying mechanism. (19th July 2019) - Qiu, Rubiao; Li, Xueyu; Qin, Kaibing; Chen, Xiong; Wang, Ruyue; Dai, Yan; Deng, Li; Ye, Yu
Abstract: Osteosarcoma (OS) refers to a malignant tumor with potential invasiveness and metastasis; however, the current chemotherapy of OS is lacking. Thus, the alternative drug for treating OS is urgent to explore. Calycosin (CC) is evidenced in our previous study to play the anti‐OS benefits for suppressing cancer cell proliferation. Consequently, further investigation of CC‐medicated anti‐invasive and metastatic effects against OS is needed. In the current study, the clinical samples of OS patients were collected for biological and staining assays, such as enzyme‐linked immunosorbent assay and polymerase chain reaction. Meanwhile, the cell line and tumor‐bearing nude mice were employed in assessing antimetastatic effects of CC against OS through biochemical tests and immunoassays. As a result, the OS patients exhibited upregulated neoplastic expressions of matrix metalloproteinase 2 (MMP2) and proliferating cell nuclear antigen (PCNA), cellular mRNAs and proteins of inhibitor of nuclear factor kappa‐B alpha (IκBα), and epithelial cell transforming sequence 2 (ECT2). In cell‐line study, CC‐treated human OS cells exhibited induced cell apoptosis, reduced cell proliferation, and cellular MMP2 and PCNA concentration, inhibited cell migration, lowered expressions of IκBα ECT2 mRNAs, and proteins. In tumor‐bearing nude mice study, CC‐treated mice resulted in the dose‐dependent reductions of tumor weights and intracellular MMP2 contents. As shown in further assays, neoplastic expressions of interleukin 6 protein, IκBα, ECT2 mRNAs, and proteins were downregulated dose‐dependently in CC‐treated tumor‐bearing mice. In conclusion, these investigative findings suggest that CC may play the potential anti‐invasive benefits against OS through suppressing metastasis‐associated IκBα/ECT2 molecular pathway.